?TRACE ELEMENTS IN TAMARINDUS INDICA-LINN AND THEIR NUTRITIONAL IMPORTANCE: ?Short Communication - Mirza, Maryam; Yaqeen, Zahra; uddin, Yaqeen; uddin, Muhammad Qadir; Badar, Yasmeen (Biological Sciences - PJSIR, 1998)
Nitric acid-hydrogen peroxide wet oxidation method was used to remove the organic matter. 1.5g sample was transferred into a 50 cm long and 2.5cm internal diameter tube, 10ml nitric acid (cone) was added and the tube was heated by plac- ing it in a cavity of aluminium block placed over a hot plate. The sample WaStaken in triplicate and a sample blank was also run side by side, when brown fumes seized to corne out. The sample was digested for about 1 h. Then 1 ml hydrogen per oxide was added dropwise to complete the oxidation. Heating was continued till the volume in the tubes was about 2 m!. It was then washed with distilled water in a 50 ml volu- metric flask and the volume was made upto the mark. Appro- priate dilutions were made for the elements having higher concentrations.